2015
DOI: 10.1002/ajmg.a.36960
|View full text |Cite
|
Sign up to set email alerts
|

FBN1 contributing to familial congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) is a relatively common, life-threatening birth defect. We present a family with recurrent CDH—paraesophageal and central—for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p. Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which parae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…These findings combined with the known pathogenic FBN1 variant allowed the diagnosis of MFS to be established. FBN1 variants and MFS have been reported in association with congenital diaphragmatic hernia (CDH), which was present in our patient (Petersons et al 2003; Faivre et al 2009; Jetley et al 2009; Beck et al 2015). However, this characteristic is not part of the revised Ghent diagnostic criteria or systemic score.…”
Section: Resultssupporting
confidence: 49%
“…These findings combined with the known pathogenic FBN1 variant allowed the diagnosis of MFS to be established. FBN1 variants and MFS have been reported in association with congenital diaphragmatic hernia (CDH), which was present in our patient (Petersons et al 2003; Faivre et al 2009; Jetley et al 2009; Beck et al 2015). However, this characteristic is not part of the revised Ghent diagnostic criteria or systemic score.…”
Section: Resultssupporting
confidence: 49%
“…14,15 More recently, a frameshift mutation in FBN1 has been reported in familial CDH cases, thus suggesting that alterations in FBN1 gene expression may lead to diaphragmatic defects. 13 In the present study, FBN1 gene expression levels were found to be significantly reduced in PPFs on D13, developing diaphragms on D15, and fully muscularized diaphragms on D18 in nitrofen-exposed fetuses compared with controls. Similarly, diaphragmatic immunofluorescence of fibrillin-1 was markedly decreased in nitrofen-exposed fetuses compared with controls, which was co-localized with the expression of the mesenchymal marker Gata4.…”
Section: Discussionsupporting
confidence: 51%
“…Beck et al 13 have reported that cases of CDH and FBN1 gene mutations were associated with sequence changes in the CDH-related gene FRAS1-related extracellular matrix 1 (FREM1). FREM1 encodes an important ECM protein that plays a critical role in the development of multiple organs including the fetal diaphragm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Ata specimen, we have identified known mutations in genes associated with disease such as cranioectodermal dysplasia (Beck et al 2015) and Greenberg skeletal dysplasia, which each produce phenotypes similar to that observed in the Ata specimen. Ata's genome also contained previously reported variants (rs41298151, p.Gly465Ala) in FREM1 and FLNB (rs1131356, p. Asp1157Asn), which are associated with congenital diaphragmatic hernia (Walczak-Sztulpa et al 2010), a relatively common, lifethreatening birth defect in which the diaphragm does not develop properly (Supplemental Table S6; Stenson et al 2014).…”
Section: Discussionmentioning
confidence: 99%